LİZENSEFALİ VE OTİZM: OLGU SUNUMU - BENBİR, Gülçin; KORKMAZ, Barış (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Lissencephaly is one of the most severe developmental brain malformations caused by incomplete neuronal migration, and characterized by loss of the normal gyral patterns in the cerebral hemispheres, prominent disorganization of the cerebral cortical cytoarchitecture, and generally associated with profound neurologic deficits and epilepsy. Affected patients usually exhibit severe delay in cognitive development and refractory epileptic seizures. Neuronal migration anomalies are important in the differential etiological diagnosis of cognitive dysfunctions including symptomatic autism. In this report, we present a case diagnosed as isolated diffuse lissencephaly, who admitted with the complaints of mental-motor retardation, and autistic disorder.